2008
DOI: 10.1152/jn.01180.2007
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of GABAA-Receptor Function and Allosteric Modulation During Development of Status Epilepticus

Abstract: Feng H-J, Mathews GC, Kao C, Macdonald RL. Alterations of GABA A -receptor function and allosteric modulation during development of status epilepticus. J Neurophysiol 99: 1285-1293, 2008. First published January 23, 2008 doi:10.1152/jn.01180.2007. Partial limbic seizures in rodents induced by pilocarpine progress from stages I-II (mouth and facial movements; head nodding) to stage III (forelimb clonus) and then progress rapidly to stages IV-V (generalized limbic seizures; rearing, and rearing with falling) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 45 publications
(48 reference statements)
3
33
0
Order By: Relevance
“…When ketamine is selected for RSE treatment following prolonged SE, it maybe typically suitable after 5-6 anticonvulsants have been found to be ineffective. This treatment choice is summarized from previous successful reports [25,26,29], and the rationale for its use is based on prolonged seizure duration, decreased numbers of active GABA receptors, gradual elevation of NMDA receptor activity, and increased numbers of NMDA receptors [14][15][16]54,55].…”
Section: Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…When ketamine is selected for RSE treatment following prolonged SE, it maybe typically suitable after 5-6 anticonvulsants have been found to be ineffective. This treatment choice is summarized from previous successful reports [25,26,29], and the rationale for its use is based on prolonged seizure duration, decreased numbers of active GABA receptors, gradual elevation of NMDA receptor activity, and increased numbers of NMDA receptors [14][15][16]54,55].…”
Section: Dosagementioning
confidence: 99%
“…In recent years, many researchers have reported that, during prolonged seizures, the number of activated GABA-A receptors on the postsynaptic membrane gradually decreases, whereas the number of inactive GABA-A receptors increases [14,15]. These changes cause a significant reduction in the efficacy of antiepileptic drugs (AEDs) that target the GABAergic system, such as diazepam, clonazepam, valproic acid, midazolam, propofol, and phenobarbital.…”
Section: Introductionmentioning
confidence: 99%
“…Ten patients (66.7%) had no lasting seizure reduction, although 3 of these patients initially had a short transient seizure reduction. Two patients decided to stop treatment before 3 months, the rest were followed in average 7.2 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) Purpose: To determine the most frequent etiology of symptomatic epilepsy in adult patients and response to antiepileptic drug therapy.…”
Section: Resultsmentioning
confidence: 99%
“…After our evaluation no one received epilepsy diagnosis. One patient had Meniere's disease, 5 Method: In two prospective, multicentre, double-blind studies, patients (ffi16 years) with genetically ascertained ULD, showing moderate to severe myoclonus (action myoclonus score >30/160), were randomized (1:1:1) to receive twice-daily BRV (study 1: 5 or 150 mg/day; study 2: 50 or 150 mg/day), or placebo. Two-week up-titration followed by 12-week maintenance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation